Synchronous frequency grid dynamics in the presence of a large-scale population of photovoltaic panels - Peruffo, A; Abate, A; Guiu, E; Panciatici, P (IEEE, 2018)
The increased relevance of renewable energy sources has modified the behaviour of the electrical grid. Some renewable energy sources affect the network in a very distributed manner: whilst each unit has little influence, a large population can have a significant impact on the global network, particularly in the case of synchronised behaviour. This work investigates the behaviour of a large, heterogeneous population of photovoltaic panels connected to the grid. We employ Markov models to represent the aggregated behaviour of the population, while the rest of the network (and its associated consumption) is modelled as a single equivalent generator, accounting for both inertia and frequency regulation. Analysis and simulations of the model show that it is a realistic abstraction, and quantitatively indicate that heterogeneity is necessary to enable the overall network to function in safe conditions and to avoid load shedding.